Separation methods for milk proteins on polyacrylamide gel electrophoresis: Critical analysis and options for better resolution. (March 2021) - Sharma, Neelima; Sharma, Rajan; Rajput, Yudhishthir S.; Mann, Bimlesh; Singh, Richa; Gandhi, Kamal
Abstract: Over the years, a number of methodological variations in polyacrylamide gel electrophoresis (PAGE) have been attempted for the separation of milk proteins. Caseins are similar in size and differ very little in net charge from each other. Also, in heated milk, κ-casein not only complexes with whey proteins but also undergoes self-polymerisation. These cause problems in the resolution of milk proteins and encouraged researchers to modify PAGE. Seven different types of PAGE, i.e., native-PAGE, urea-PAGE, reducing-sodium dodecyl sulphate (SDS)-PAGE, non-reducing-SDS-PAGE, urea-SDS-PAGE, tricine-PAGE, and two-dimensional electrophoresis (2DE), are reviewed with particular emphasis on the pattern of milk protein electrophoretograms, merits, demerits and applications. Although the literature suggests that SDS-PAGE is increasingly used for separating milk proteins, other forms of PAGE have their own advantage. This review can act as a quick screening aid for researchers in selecting an appropriate type of PAGE for the separation of milk proteins for different purposes.